Enhanced Arabidopsis pattern-triggered immunity by overexpression of cysteine-rich receptor-like kinases - Yeh, Yu-Hung; Chang, Yu-Hsien; Huang, Pin-Yao; Huang, Jing-Bo; Zimmerli, Laurent (Frontiers in Plant Science, 2015)
Upon recognition of microbe-associated molecular patterns (MAMPs) such as the bacterial flagellin (or the derived peptide flg22) by pattern-recognition receptors (PRRs) such as the FLAGELLIN SENSING2 (FLS2), plants activate the pattern-triggered immunity (PTI) response. The L-type lectin receptor kinase-VI.2 (LecRK-VI.2) is a positive regulator of Arabidopsis thaliana PTI. Cysteine-rich receptor-like kinases (CRKs) possess two copies of the C-X8-C-X2-C (DUF26) motif in their extracellular domains and are thought to be involved in plant stress resistance, but data about CRK functions are scarce. Here we show that Arabidopsis overexpressing the LecRK-VI.2-responsive CRK4, CRK6 and CRK36 demonstrated an enhanced PTI response and were resistant to virulent bacteria Pseudomonas syringae pv. tomato DC3000. Notably, the flg22-triggered oxidative burst was primed in CRK4, CRK6, and CRK36 transgenics and up-regulation of the PTI-responsive gene FLG22-INDUCED RECEPTOR-LIKE 1 (FRK1) was potentiated upon flg22 treatment in CRK4 and CRK6 overexpression lines or constitutively increased by CRK36 overexpression. PTI-mediated callose deposition was not affected by overexpression of CRK4 and CRK6, while CRK36 overexpression lines demonstrated constitutive accumulation of callose. In addition, Pst DC3000-mediated stomatal reopening was blocked in CRK4 and CRK36 overexpression lines, while overexpression of CRK6 induced constitutive stomatal closure suggesting a strengthening of stomatal immunity. Finally, bimolecular fluorescence complementation and co-immunoprecipitation analyses in Arabidopsis protoplasts suggested that the plasma membrane localized CRK4, CRK6 and CRK36 associate with the PRR FLS2. Association with FLS2 and the observation that overexpression of CRK4, CRK6, and CRK36 boosts specific PTI outputs and resistance to bacteria suggest a role for these CRKs in Arabidopsis innate immunity.